Species niches, not traits, determine abundance and occupancy patterns: A multi‐site synthesis. Issue 2 (10th November 2019) - Marino, Nicholas A. C.; Céréghino, Régis; Gilbert, Benjamin; Petermann, Jana S.; Srivastava, Diane S.; de Omena, Paula M.; Bautista, Fabiola Ospina; Guzman, Laura Melissa; Romero, Gustavo Q.; Trzcinski, M. Kurtis; Barberis, Ignacio M.; Corbara, Bruno; et al.
Abstract: Aim: Locally abundant species are usually widespread, and this pattern has been related to properties of the niches and traits of species. However, such explanations fail to account for the potential of traits to determine species niches and often overlook statistical artefacts. Here, we examine how trait distinctiveness determines the abilities of species to exploit either common habitats (niche position) or a range of habitats (niche breadth) and how niche position and breadth, in turn, affect abundance and occupancy. We also examine how statistical artefacts moderate these relationships. Location: Sixteen sites in the Neotropics. Time period: 1993–2014. Major taxa studied: Aquatic invertebrates from tank bromeliads. Methods: We measured the environmental niche position and breadth of each species and calculated its trait distinctiveness as the average trait difference from all other species at each site. Then, we used a combination of structural equation models and a meta‐analytical approach to test trait–niche relationships and a null model to control for statistical artefacts. Results: The trait distinctiveness of each species was unrelated to its niche properties, abundance and occupancy. In contrast, niche position was the main predictor of abundance and occupancy; species that used the most common environmental conditions found across bromeliads were locally abundant and widespread. Contributions of niche breadth to such patterns were attributable to statistical artefacts, indicating that effects of niche breadth might have been overestimated in previous studies. Main conclusions: Our study reveals the generality of niche position in explaining one of the most common ecological patterns. The robustness of this result is underscored by the geographical extent of our study and our control of statistical artefacts. We call for a similar examination across other systems, which is an essential task to understand the drivers of commonness across the tree of life.